Current Expected Credit Losses and consumer loans - Granja, João; Nagel, Fabian (Journal of Accounting and Economics, 2025)
We use data from TransUnion, a large U.S. credit bureau covering millions of individual consumer loans, to examine the transition to the Current Expected Credit Loss (CECL) accounting standard and to provide novel evidence about the impact that raising reserve requirements has on banks’ pricing and lending decisions in the U.S. consumer lending market. We find that greater reserve requirements following the adoption of CECL induce a statistically significant but economically moderate increase in loan interest rates. The effects are more pronounced for weakly-capitalized banks and even more so for underprivileged individuals borrowing from weakly-capitalized banks. Our evidence informs the ongoing policy debate between standard setters and members of the financial industry about the potential effects of CECL on credit markets.